2022
DOI: 10.3389/fnut.2022.1050011
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin E concentration in breast milk in different periods of lactation: Meta-analysis

Abstract: ObjectiveThis study systematized information about vitamin E concentration in healthy breast milk during different stages of lactation in order to support the strategies of protecting postpartum women and infants.MethodsStudies published before April 30th, 2021, which detected vitamin E concentration in breast milk of healthy women by High Performance Liquid Chromatography (HPLC) or Ultra High Performance Liquid Chromatographic (UHPLC), were evaluated. The databases of CNKI (Chinese), WanFang Data (Chinese), V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…By contrast, the levels of total fat and oligosaccharides such as 3 ′ -fucosyllactose increase throughout lactation [4,5]. Presumably, the dynamics surrounding the intake of human milk components indicate the precise needs for nutrients Nutrients 2024, 16, 1710 2 of 17 of infants. For instance, concentrations of human milk total amino acids, which are the building blocks of infant body tissue, in 5-6 months of lactation are about two thirds of those available in the first month [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the levels of total fat and oligosaccharides such as 3 ′ -fucosyllactose increase throughout lactation [4,5]. Presumably, the dynamics surrounding the intake of human milk components indicate the precise needs for nutrients Nutrients 2024, 16, 1710 2 of 17 of infants. For instance, concentrations of human milk total amino acids, which are the building blocks of infant body tissue, in 5-6 months of lactation are about two thirds of those available in the first month [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few review studies that have specifically investigated the longitudinal changes in minerals and vitamins in human milk. For instance, Dror et al focused on iodine and vitamin B-12 [ 13 , 14 ], Zhang H et al examined vitamin A [ 15 ], Xi Y et al reported on vitamin E [ 16 ], and Gidrewicz et al provided data on calcium and phosphorus from 1 to 12 postnatal weeks [ 17 ]. Another study by Yang et al surveyed nine minerals, but they only analyzed milk samples beyond 2 postnatal weeks: by then, the samples contain mature milk.…”
Section: Introductionmentioning
confidence: 99%